MEDIA BANTU PEMBELAJARAN BUDIDAYA TANAMAN SECARA HIDROPONIK DENGAN METODE DEMON-DISCO LEARNING BERBASIS ANDROID (studi kasus : SMK Kristen Terang Bangsa) - Setiyo Prihatmoko; Sumaryanto; Daniel Novianto (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
ABSTRACT The use of mobile devices with the Android operating system which are used as supporting media and supplements in improving learning outcomes combined with demonstration methods and discovery learning or demon-disco learning is needed to help students improve learning outcomes in hydroponic plant cultivation vocational competency subjects at SMK. Kristen Terang Bangsa, because the use of android-based applications can provide new experiences regarding the use of information and communication technology, as well as provide opportunities for students to be able to learn more independently. The concept chosen as a learning medium is to present material about understanding, introduction to parts, types, and quizzes containing questions about hydroponic cultivation of plants. This research uses the Research and Development (RnD) product development method, using 6 out of 10 research stages, namely potentials and problems, data collection, product design, design validation, design improvement, product testing. The result of this research is to produce learning media in the form of android-based applications. The validity value of the media expert is 2.6 which is declared feasible, while the validity value of the material expert is 3.6 which is declared feasible, and is able to increase the average value in the hydroponic plant cultivation vocational competency subject at the Terang Bangsa Christian Vocational School which Initially 67 (with 13 students who had not reached the KKM) to 80 (with 4 students who had not reached the KKM).